Towards the development of source separation and valorization of human excreta? Emerging dynamics and prospects in France - Joveniaux, Aurélie; Legrand, Marine; Esculier, Fabien; De Gouvello, Bernard (Frontiers in Environmental Science, 2022)
The source separation of human excreta (urine and/or feces) offers an alternative to conventional sanitation systems (flush toilets/public sewers) that is appealing in several respects, especially in environmental terms and for agricultural purposes, as a source of natural fertilizer from local and renewable resources. In France, systems for the separate collection of human excreta have previously been confined to the rural sphere and mainly implemented at the individual scale. However, since the 2010s, experimental projects in excreta source separation have been observed in urban areas, at the scale of individual houses and collective buildings, or even neighborhoods. This article, drawing on interdisciplinary social science research conducted within the French research program OCAPI (on ecological transition in nutrition/excretion systems), investigates these innovative projects for the source separation of human excreta in urban areas. Our work lies on a territorial approach, based on a cross-sectional analysis of experimental projects in three cities (Paris, Bordeaux and Grenoble), complemented by the mobilization of the “multi-level perspective” and the “technological innovation systems” frameworks. We study the trajectory and factors of development of source separation in France, its implementation dynamics and territorialisation pathways. Our analysis shows that source separation is still in an emerging phase in France. It is currently experimented in cities through diversified projects and approaches. This diversity applies both to socio-technical choices and territorial embeddedness’ forms. Adopting a prospective point of view, we then point out main obstacles and drivers to the scaling-up of this innovative practice: beyond technical issues, shared social values, stakeholder alignment issues and organizational challenges are essential. Finally, we consider possible directions for its development, ranging from the spread of a homogeneous solution to the continuation of a diversity of approaches on different territories.